A role for melatonin in maintaining the pro- and anti-inflammatory balance by influencing leukocyte migration and apoptosis in carp. Issue 1 (November 2015) - Kepka, Magdalena; Szwejser, Ewa; Pijanowski, Lukasz; Verburg-van Kemenade, B.M. Lidy; Chadzinska, Magdalena
Abstract: Melatonin is responsible for the synchronization of many physiological processes, including the immune response. Here we focus on the expression of melatonin MT1 receptors in/on leukocytes, and on the effects of melatonin administration on the inflammatory processes of carp. For the first time, we showed that fish leukocytes express MT1 receptors, implicating direct responsiveness to melatonin stimulation. Moreover, both in vitro and in vivo, melatonin modulated the immune response. The most potent effects of melatonin concerned the regulation of leukocyte migration. Melatonin reduced chemotaxis of leukocytes towards CXC chemokines in vitro . In vivo, during zymosan induced peritonitis, i.p. administration of melatonin reduced the number of neutrophils. This correlated with a melatonin-induced decrease of gene expression of the CXCa chemokine. Moreover, melatonin induced a decrease of the respiratory burst in inflammatory leukocytes. Although these data do suggest a potent anti-inflammatory function for this hormone, melatonin-induced inhibition of leukocyte apoptosis clearly indicates towards a dual function. These results show that also in carp, melatonin performs a pleiotropic and extra-pineal function that is important in maintaining the delicate pro- and anti-inflammatory balance during infection. They furthermore demonstrate that neuroendocrine–immune interaction via melatonin is evolutionary conserved. Highlights: Carp lymphoid organs and leukocytes express the MT1 melatonin receptor. Melatonin reduces chemotaxis of leukocytes towards CXC chemokines. During peritonitis melatonin reduces migration of neutrophils. Expression of the CXCa gene Melatonin decrease the respiratory burst in inflammatory leukocytes. Melatonin affects leukocyte apoptosis.